La reemergencia del discurso nacional-popular en la nueva izquierda latinoamericana: Para una discusión de los movimientos nacional-populares - Cancino, Hugo (Diálogos Latinoamericanos, 2008)
In this article we analyse the reemergence of the national discourse and popular. The national-popular movements that are a recurrent phenomenon in the history of Latin America. Revolutions and the most significant social movements of the twentieth century were popular and national movements. In our view the national and popular movements that lead Hugo Chaves and Evo Morales represent a new left compared to of the traditional left and the renewed call left. These movements, the people built as historical subject and fight for the construction of new State, by a radical democracy, which replaced the State and National Creole oligarchy that excluded indigenous and mestizo of power and wealth.